Educational Technology and Learning Analytics: Improving Student Performance through Digital Innovation - Muhammad Uzair Khalid; Sana Farooq (Global Journal of Multidisciplinary and Applied Sciences, 2023)
Educational technology (EdTech) and learning analytics are reshaping how institutions support student success by turning digital learning traces into actionable insights. Learning analytics—defined as the collection, analysis, interpretation, and communication of learner data to improve teaching and learning—enables early identification of academic risk, personalization of content, and continuous improvement of instructional design. However, performance gains are not automatic: impact depends on data quality, valid learning measures, instructor capacity, student trust, and governance frameworks that protect privacy and ensure responsible use. This article synthesizes key mechanisms through which digital innovation improves learning outcomes (feedback loops, adaptive practice, predictive risk models, and evidence-based teaching), highlights implementation barriers commonly faced in resource-constrained contexts, and proposes a practical roadmap for institutions to deploy analytics ethically, inclusively, and effectively